2022
DOI: 10.3390/cells11111735
|View full text |Cite
|
Sign up to set email alerts
|

Reducing PDK1/Akt Activity: An Effective Therapeutic Target in the Treatment of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a common age-related neurodegenerative disease that leads to memory loss and cognitive function damage due to intracerebral neurofibrillary tangles (NFTs) and amyloid-β (Aβ) protein deposition. The phosphoinositide-dependent protein kinase (PDK1)/protein kinase B (Akt) signaling pathway plays a significant role in neuronal differentiation, synaptic plasticity, neuronal survival, and neurotransmission via the axon–dendrite axis. The phosphorylation of PDK1 and Akt rises in the brain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 198 publications
0
5
0
Order By: Relevance
“…In addition to clear Aβ by inducing autophagy, the Protein kinase B (Akt) signaling pathway also causes abnormalities in central insulin signaling and NTFs [21,22]. Glucose transporter 4 (GLUT4) is transported to the neuron membrane under the induction of Akt, which improves insulin transport to brain neurons in learning and memory state [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to clear Aβ by inducing autophagy, the Protein kinase B (Akt) signaling pathway also causes abnormalities in central insulin signaling and NTFs [21,22]. Glucose transporter 4 (GLUT4) is transported to the neuron membrane under the induction of Akt, which improves insulin transport to brain neurons in learning and memory state [23].…”
Section: Discussionmentioning
confidence: 99%
“…mGluR5 supports long-term changes in synaptic strength by regulating the transcription and translation of essential synaptic proteins [49]. Other identi ed core targets AKT1, EGFR, MAPK1 and CNR1 (CB1) have been approved to take part in enhancing learning and memory performance through regulation [50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…85 Studies have revealed that TACE has been associated with inammatory diseases, such as Alzheimer's disease, as increased plasma TACE activity has been observed in subjects with mild cognitive impairment. [86][87][88][89] Inhibition of TACE has the potential to mitigate TNFa levels and amyloid b deposition in Alzheimer's disease, 90 while elevated cerebrospinal uid (CSF) levels of TACE activity and soluble TNF receptors have been observed in patients with Alzheimer's disease. 87 TACE is a multidomain metalloproteinase that processes tumor necrosis factor and a host of other proteins.…”
Section: Tnf-a Converting Enzyme (Tace)mentioning
confidence: 99%